2016
DOI: 10.1016/j.ejmech.2015.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of antiviral molecules for dengue: In silico search and biological evaluation

Abstract: Background: Dengue disease is a global disease that has no effective treatment. The dengue virus (DENV) NS2B/NS3 protease complex is a target for designing specific antivirals due to its importance in viral replication and its high degree of conservation.Methods: NS2B/NS3 protease complex structural information was employed to find small molecules that are capable of inhibiting the activity of the enzyme complex. This inhibitory activity was probed with in vitro assays using a fluorescent substrate and the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Nevertheless, many peptidic or modified peptidic molecules have been discovered to have good NS2B/NS3pro inhibition activities [15,[24][25][26][27][28][29][30]. In addition, there are also reports of potent small molecule NS2B/ NS3pro inhibitors from natural products (panduratin [31], agathisflavone and quercetin [32]), from synthetic medicinal chemistry (dehydronaphthalene [33], benzimidazole [34], and thiadiazoloacrylamide [35]) or from the utilisation of computational methods [36][37][38][39].…”
mentioning
confidence: 99%
“…Nevertheless, many peptidic or modified peptidic molecules have been discovered to have good NS2B/NS3pro inhibition activities [15,[24][25][26][27][28][29][30]. In addition, there are also reports of potent small molecule NS2B/ NS3pro inhibitors from natural products (panduratin [31], agathisflavone and quercetin [32]), from synthetic medicinal chemistry (dehydronaphthalene [33], benzimidazole [34], and thiadiazoloacrylamide [35]) or from the utilisation of computational methods [36][37][38][39].…”
mentioning
confidence: 99%
“…During the developmental stages of more effective medication candidates, it is likely to have various unsuccessful attempts at reaching a promissory compound for further study and clinical trials, on account of pharmacokinetic limitations, undesirable toxicities, and instabilities, properties that can be detected by using specialized programs, such as FAF-Drugs3 [ 42 ]. This server is able to predict ADME/Tox properties, such as absorption, distribution, metabolism, excretion and toxicity, as well as descriptors to ultimately reduce time, resources and costs on apparent promising candidates.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, not only viral proteins but also human factors could also be interrupted by these active compounds, raising the possibility of adverse side effects. Although many studies have revealed the ability of potent compounds that could interrupt several proteins and host factors in human cells [7,14,15,[24][25][26], one of the challenging quests is to search for the probable protein targets of active compounds, which is an arduous step for drug discovery and design [27][28][29][30][31]. Once discovered, the potent molecules can be further optimized to increase their efficiency using the information on the interaction between the compound and key residues in the target binding site.…”
Section: Introductionmentioning
confidence: 99%